Metallic ions as therapeutic agents in tissue engineering scaffolds: an overview of their biological applications and strategies for new developments - Mourino, Viviana; Pablo Cattalini, Juan; Boccaccini, Aldo R. (Journal of the Royal Society Interface, 2012)
This article provides an overview on the application of metallic ions in the fields of regenerative medicine and tissue engineering, focusing on their therapeutic applications and the need to design strategies for controlling the release of loaded ions from biomaterial scaffolds. A detailed summary of relevant metallic ions with potential use in tissue engineering approaches is presented. Remaining challenges in the field and directions for future research efforts with focus on the key variables needed to be taken into account when considering the controlled release of metallic ions in tissue engineering therapeutics are also highlighted. © 2011 The Royal Society.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.metall
Keywords: Bone; Controlled release; Drug delivery; Metallic ions; Scaffolds; Tissue engineering